Water fluoridation, dental caries and parental ratings of child oral health. Issue 6 (12th September 2021) - Foley, Michael Anthony; Sexton, Christopher; Spencer, Andrew John; Lalloo, Ratilal; Do, Loc Giang
Abstract: Objectives: Previous studies have identified many demographic, socioeconomic, behavioural and clinical variables associated with subjective parental ratings of child oral health. This study investigated associations between children's lifetime exposure to fluoridated drinking water (LEFW) and dental caries prevalence and parental ratings. Methods: Australia's National Child Oral Health Study 2012–2014 conducted oral epidemiological examinations for 24 664 children aged 5–14 and investigated risk factors for child oral health and disease through questionnaires. Parents also subjectively rated their child's oral health. This cross‐sectional study estimated prevalence ratios for associations between LEFW and prevalence of dental caries in the primary and permanent dentitions and parental oral health ratings for 5–8 year old and 9–14 year old children. E‐value sensitivity analyses helped assess whether observed effect sizes may have arisen through unmeasured confounding. Results: Children aged 5–8 with 0%–10% or 11%–89% LEFW are respectively 1.5 (95% CI 1.2–1.8) and 1.5 (95% CI 1.1–2.0) times more likely than children with 90%–100% LEFW to receive a fair or poor parental oral health rating. Children aged 9–14 with 0%–10% or 11%–89% LEFW are 1.2 (95% CI 1.0–1.4) times more likely than children with 90%–100% LEFW to receive a fair or poor parental oral health rating. Children aged 5–8 with 0%–10% or 11%–89% LEFW are respectively 1.4 (1.3–1.6) and 1.3 (95% CI 1.1–1.4) times more likely than children with 90%–100% LEFW to experience caries in their primary teeth. Children aged 9–14 with 0%–10% or 11%–89% LEFW are respectively 1.4 (95% CI 1.3–1.5) and 1.1 (95% CI 1.0–1.2) times more likely than children with 90%–100% LEFW to experience caries in their permanent teeth. Conclusions: Longer lifetime exposure to fluoridated drinking water is causally associated with a lower childhood dental caries prevalence and more positive parental ratings of child oral health. The associations are stronger for younger children.